2019
DOI: 10.1002/ceat.201900180
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Mitigation of Methane Emissions from Pressure Relief Valves of a Biogas Plant

Abstract: The two‐year monitoring (732 days) of operational methane emissions from pressure relief valves of the gasholders from an agriculture biogas plant is presented. The monitoring aimed at the identification of major factors influencing the emissions and the effect of mitigation measures deduced from the results. The determined emission factors from the valves of both gastight covered digesters are 1.8 and 0.6 % CH4 loss for the first and second year of investigation, respectively. The emission rates strongly depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Portable GC-MS (gas chromatography-mass spectroscopy) [239] CH 4 emissions from pressure relief valves of an agricultural biogas plant Flow velocity and temperature sensors [240] Ammonia in biogas Impedance measurement of biogas condensate in the gas room above the digester [241] Dissolved active trace elements in biogas Total reflection X-ray fluorescence spectroscopy in dried digester slurry [238] H 2 S in biogas Gas responsive nano-switch (copper oxide composite) [242] Microbial communities depend on the substrate combinations Sequencing of the 16S rRNA, biodegradable feedstock samples from eight different biogas plants [243] Controlling gas pressure in the digester Programmable logic controller (PCL) [244] Ammonia in biomethane The currently available technologies do not enable the monitoring of all operational parameters of the biogas plant. Therefore, samples have to be collected from the biogas plant and analyzed in individual facilities (off-line monitoring) [142].…”
Section: Measurement Methods Referencementioning
confidence: 99%
“…Portable GC-MS (gas chromatography-mass spectroscopy) [239] CH 4 emissions from pressure relief valves of an agricultural biogas plant Flow velocity and temperature sensors [240] Ammonia in biogas Impedance measurement of biogas condensate in the gas room above the digester [241] Dissolved active trace elements in biogas Total reflection X-ray fluorescence spectroscopy in dried digester slurry [238] H 2 S in biogas Gas responsive nano-switch (copper oxide composite) [242] Microbial communities depend on the substrate combinations Sequencing of the 16S rRNA, biodegradable feedstock samples from eight different biogas plants [243] Controlling gas pressure in the digester Programmable logic controller (PCL) [244] Ammonia in biomethane The currently available technologies do not enable the monitoring of all operational parameters of the biogas plant. Therefore, samples have to be collected from the biogas plant and analyzed in individual facilities (off-line monitoring) [142].…”
Section: Measurement Methods Referencementioning
confidence: 99%
“…Emissions can come from water handling facilities, gas engine exhausts, gas flaring, leaks from pipes, biogas upgrading units, tanks, etc., or from deliberate venting (Angelidaki et al, ; Duren et al, ; Fredenslund et al, ; Liebetrau et al, ; Samuelsson et al, ; Scheutz & Fredenslund, ). Some emissions can be single large leaks or long‐lasting bursts from pressure relief valves (Reinelt & Liebetrau, ). In particular, Kvist and Aryal () found that water scrubbers and pressure relief valves were especially significant sources of emissions, a finding similar to findings around many unconventional natural gaswells.…”
Section: Practical Emission Reduction and Removal—tractable Emissionsmentioning
confidence: 99%
“…32 Although emissions from the biomethane supply chain are comparable to oil and natural-gas production in terms of Tg CH 4 year À1 , the production-normalized emission rate is considerably higher. This could be due to a variety of factors, including poorly managed production facilities; a lack of attention to the biomethane industry resulting in lower investments for modernization, operation, and monitoring; and employment of highly skilled plant operators 16,21 when compared with oil and natural gas. In addition, poor design and management of feedstock and digestate storage units 33 as well as a limited interest in infrastructure emissions may result in higher emission rates compared with the amount of gas produced.…”
Section: Total Supply Chain Emissionsmentioning
confidence: 99%
“…These have found that emissions from biomethane facilities can be up to 97 kg h À1 CH 4 . 4,[16][17][18][19][20][21][22][23][24] However, a comprehensive evaluation by characterizing the distribution of CH 4 emissions at each biomethane and biogas supply chain stage remains unclear.…”
Section: Introductionmentioning
confidence: 99%